Effects of plyometric training on skill-related physical fitness in badminton players: A systematic review and meta-analysis - Deng, Nuannuan; Soh, Kim Geok; Abdullah, Borhannudin Bin; Huang, Dandan (Elsevier, 2024)
Skill-related physical fitness significantly correlates with sports performance. Plyometric training (PT) is an effective method for improving physical fitness in athletes. However, its impact on skillrelated physical fitness in badminton players remains uncertain. Therefore, this systematic review and meta-analysis aimed to evaluate the effectiveness of PT on skill-related physical fitness in badminton players. Five electronic databases (Web of Science, PubMed, SCOPUS, MEDLINE, and SPORTSDiscus) were searched until February 2024. A PICOS approach was used to identify inclusion criteria, (1) healthy badminton players, (2) a PT program, (3) an active control group, (4) a measure of skill-related physical fitness before and after PT, and (5) randomized controlled studies. The PEDro scale was used to assess the methodological quality of PT studies, while the level of evidence certainty was determined through the GRADE framework. The calculation of effect sizes (ESs) was based on mean values and standard deviations, and heterogeneity was measured with the I 2 statistic. The extended Egger’s test was employed to check for publication bias. Eleven studies comprising 445 badminton players were eligible for inclusion. The analysis revealed significant small-to-moderate effects of PT on power (ES = 0.60, p < 0.001), agility (ES = 0.96, p < 0.001), speed (ES = 0.63, p = 0.001), and balance (ES = 0.89; p = 0.013). However, no significant effect was observed for reaction time (ES = 0.56; p = 0.189). The certainty of evidence for outcomes was graded as either low or very low. In conclusion, our findings demonstrate that PT improved power, agility, speed, and balance, but not reaction time in badminton players. However, the small number of studies and the very low to low certainty evidence mean that these results need to be interpreted with caution.